TRA VISIONS 2020 - CROSS MODALITY AWARD WINNER - Nikolaou, Paraskevas (My University, 2026)
Title: Controlling the possible spread of infectious diseases through the air transportation network: a dynamic network approach (https://www.travisions.eu/TRAVisions/young_researcher_results_2020/#:~:text=Micol%20Biscotto%2C%20project%20manager%20at,with%20the%20support%20of%20Prof.)
Keywords: Sciences